2006
DOI: 10.1073/pnas.0506655103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the bacterial microbiota in the human stomach

Abstract: The microbiota of the human stomach and the influence of Helicobacter pylori colonization on its composition remain largely unknown. We characterized bacterial diversity within the human gastric mucosa by using a small subunit 16S rDNA clone library approach and analyzed 1,833 sequences generated by broad-range bacterial PCR from 23 gastric endoscopic biopsy samples. A diverse community of 128 phylotypes was identified, featuring diversity at this site greater than previously described. The majority of sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
872
12
26

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 955 publications
(977 citation statements)
references
References 29 publications
67
872
12
26
Order By: Relevance
“…Consistent with previous studies (Bik et al, 2006;Andersson et al, 2008), the human gastric bacterial community is very rich but uneven, strongly dominated by only four phyla, namely, Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with previous studies (Bik et al, 2006;Andersson et al, 2008), the human gastric bacterial community is very rich but uneven, strongly dominated by only four phyla, namely, Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to H. pylori, the stomach can also contain transient oral, esophageal or intestinal bacteria. To date, the few studies that have explored the microbiota of the human stomach using molecular methods (Bik et al, 2006;Andersson et al, 2008) have shown that the gastric community is highly dominated by Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes, with H. pylori being the single dominant bacteria in patients of positive H. pylori status. Bik et al (2006) sequenced 1833 bacterial clones from gastric biopsy samples from 23 US patients and found eight bacterial phyla (128 phylotypes) with no differences in richness by H. pylori status and with 7 of 11 patients of apparent negative H. pylori status having H. pylori clones.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this diversity, one single genus (i.e., Helicobacter) was by far the most predominant (~ 98% of all gastric microbiota). These results are in accordance with one study that showed that the human stomach is also home of a diverse microbiota, although the genus Helicobacter (H. pylori only) constituted only 42% of all sequences analyzed (Bik et al 2006).…”
Section: The Gi Microbiota Of Dogssupporting
confidence: 81%
“…The study of the human microbiome focuses predominantly on bacterial flora (Bik et al, 2006;Gao et al, 2007;Costello et al, 2009); however, there are numerous reports of viral communities inhabiting different body sites (Bachrach et al, 2003;Breitbart et al, 2003;Bik et al, 2006;Gao et al, 2007;Breitbart et al, 2008;Costello et al, 2009;Reyes et al, 2010). Although there are viruses of Eukarya inhabiting these sites (Victoria et al, 2009;Foulongne et al, 2012;Lysholm et al, 2012), the majority of the viruses that have been identified in these habitats are bacteriophage (Breitbart et al, 2008;Willner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%